Vontade política, razão comunicativa e educação: análise sobre o sentido político-educacional da reforma do ensino médio - Lei 13.415/17 - Venturelli, Sandra Olades Martins (Universidade Federal de São Carlos, 2023)
This thesis aims to analyze the formation of political will in contemporary society within formal education. Considering the importance of developing a critical potential for the formative process, we analyze the potentialities of a political will formation in the educative process that can be constituted in an emancipatory action and face the domain of strategic and technical-instrumental rationality over discursive rationality. We evaluate that emancipation in the process of political will formation in schools might be related to the decision processes of the institutions that wield power, such as the State. Its actions should aim to allow social interaction and build accessible communication without undiscussed impositions but consensually evaluated instead. As the determination of Educational Public Policies orients formal education (schooling), we search to identify the rational fundaments which sustain the educational-political processes once we consider being necessary rationality created and expressed by intersubjectivity. We analyze the hasty approval procedures of High School Reform, Law nº 13.415/17, to identify if there were any deformation of emancipatory projects in the education system, favoring the relations with the market and neoliberal projects. For this thesis's development, we employ the conceptual theoretical fundaments of Jürgen Hamermas's thinking, which offer indispensable elements to comprehend the structure that holds the rationality of the modern world. Through bibliographic research, we develop the theoretical framework and advance on constructing the necessary concepts for this thesis understanding. We conducted the documental analysis through publicized institutional documents referring to educational policies and curriculum orientation, such as laws, decrees, and provisional measures.
Political will, communicative rationality, and education: analysis of the political-educational significance of the high school reform - Law 13.415/17
Keywords: Vontade política; Educação; Políticas públicas educacionais; Razão comunicativa; Political will; Education; Public policies of education; Communicative rationality; CIENCIAS HUMANAS::EDUCACAO